Exploring the Potential of Affiliate Marketing for Online News Portals in Albania (European Journal of Marketing and Economics, 2024)
This paper explores the strategic and economic potential of affiliate marketing as a revenue-generating model for online news portals in Albania. As traditional advertising revenues decline, media organizations increasingly seek alternative monetization methods compatible with the digital landscape. Affiliate marketing—a performance-based model where publishers earn commissions for directing traffic or sales to advertisers—presents a scalable, low-risk opportunity for digital media platforms. Focusing on prominent Albanian news websites, the study investigates how affiliate strategies can be effectively implemented to enhance business sustainability while preserving editorial integrity. Key research questions include identifying the most appropriate affiliate models (CPC, CPA, CPL), determining content formats best suited for affiliate integration, and evaluating the readiness of Albanian digital infrastructure and audience behavior for such models. Using a descriptive research methodology and qualitative insights from local market practices, the findings suggest that affiliate marketing offers viable revenue diversification potential for Albanian media. However, success depends on transparency, audience trust, and alignment between content and commercial partnerships. The study provides actionable recommendations for digital media entrepreneurs, marketing strategists, and policy stakeholders aiming to foster innovation and economic resilience in Albania’s online media sector.
Keywords: Affiliate Marketing, Online News Portals, Digital Media Strategy, Performance Marketing, Albania, E-commerce Potential